SITUATIONAL ASPECTS OF CURRENT MOOD – AFFECTIVE CHANGES DURING RESTING STATE AND MOOD INDUCTION - Sokić, Jelena; Milinković, Ivana; Novović, Zdenka; Biro, Mikloš (Primenjena psihologija, 2017)
Most of the cognitive theories suggest that depressive mood occurs in response to stressful, even low-intensity, environmental events, while the assumptions of recent neurobiological models center around the idea that depressive mood can be elicited in the absence of any external stimuli. The goal of this study was to examine the assumptions stemming from two different theoretical perspectives, regarding contribution of different situational aspects which could lead to the changes in current emotional status in vulnerable individuals, and eventually to the development of depressive symptoms. The sample consisted of 72 participants, average age of 25 (SD = 4.18), of which 75.3% were females. In the first group (N = 36), the standard procedure of mood induction with music was applied, while in the other group (N = 36) the procedure of behavioral resting state was used. Our results showed that both procedures led to the changes of current emotional status. Moreover, the interaction effect of experimental condition, time, and vulnerability level was significant. Both experimental conditions led to the significant decrease in positive affect, regardless of vulnerability level. However, in the resting condition, vulnerable participants reported somewhat higher negative affect. The results are partially in line with the cognitive theories, but also support the assumptions that resting state can provide ideal conditions for focusing on maladaptive cognitions.